Isolation and Propagation of a Human CD133 Colon Tumor-Derived Cell Line with Tumorigenic and Angiogenic Properties - Nalú Navarro-Alvarez (Cell Transplantation, 2010)
It has been proposed in human colorectal cancers (CRC) a minority subset of cancer cells within tumors able to initiate tumor growth, defined as cancer stem cells (CSC). Solid human primary colonic and its ovarian metastatic cancer tissues were collected from fresh surgical samples and subsequent xenografts were established in nonobese diabetic/severe combined immunodeficient (NOD/SCID) mice. The resulting tumors were disaggregated into single-cell suspensions and a CD133 - cell line (NANK) was newly established and analyzed by flow cytometry. Surface markers of progenitor cells were immunophenotypically analyzed, and expression of stem cell and cancer-related genes was characterized. Secreted angiogenesis-associated molecules were investigated by proteomic array technology. Finally, different numbers of NANK were implanted and their tumor-initiating properties were investigated in NOD/SCID mice. Intraperitoneal injection of NANK in NOD/SCID mice induced tumors with developing progressive peritoneal dissemination and ascites. NANK cells maintained a differentiated phenotype and reproduced the full morphologic and phenotypic heterogeneity of their parental lesions. Noticeably, NANK lacked the expression of conventional CSC markers CD133 and CD44, self-renewal genes Oct-4 and Nanog, but showed the expression of an important gastrointestinal development marker CDX-2 and BMI-1 that is essential in regulating the proliferative activity of normal and leukemic stem cells. In addition, NANK secreted high amounts of important angiogeneic cytokines. These results provide a novel and extensive model in human CSC for studying the generation and maintenance of phenotypic heterogeneity in CRC.